Processing and structural health monitoring of a composite overwrapped pressure vessel for hydrogen storage - Rocha, Helena Cristina Lopes (2023)
A process and Structural Health Monitoring system was implemented on a Composite Overwrapped Pressure Vessel (COPV) for hydrogen storage at 350 bar to be used in a fuel-cell system of an Unmanned Aerial Vehicle. This work reports the embedment strategy of optical fibre Bragg grating (FBG) sensors to monitor the full life cycle of the vessel, consisting of an aluminium liner and a wound carbon fibre reinforced polymer composite overwrap. A FBG sensing array, bonded on the aluminium liner circumferential section, was covered with a localised unidirectional prepreg composite tape, enabling composite winding and curing monitoring. The sensing array strategy allowed to detect and locate Barely Visible Impact Damage resulting from drop-weight impact tests, based on the ratio of the residual strain amplitude between FBG sensor pairs. Errors as small as 17 mm and up to 56 mm were determined between the predicted and ‘real’ impact locations. To simulate the real-life operational pressure charging and discharging cycles, the COPV was subjected to cycling testing at different pressure ranges. The FBG sensors were able to monitor a total of 20 980 pressure cycles, revealing a linear response to the applied pressure, and remained operational after COPV failure. Furthermore, the FBG sensing array was able to detect the residual plastic strain caused in the aluminium liner by the autofrettage process that the COPV was subjected to prior to pressure cycling, at 600 bar for 2 min, to improve its fatigue performance. This manuscript also reports the COPV structural design by Finite Element Modelling (FEM), its manufacturing process and burst pressure testing for the FEM analysis validation. A small difference of 0.7% was found between the simulated and experimental determined burst pressure of 1061+-26 bar.